Special interest groups versus voters and the political economics of attention - Patrick Balles; Ulrich Matter; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2020)
We examine whether representatives are more likely to serve long-term campaign donors instead of constituents during times of low media attention to politics. Based on 425 roll calls between 2005 and 2014 in the US House of Representatives, we show that representatives are more likely to vote with special interests and against constituency interests when the two are in conflict. Importantly, the latter effect is significantly larger when there is less attention on politics due to exogenous newsworthy events. The opportunistic behavior seems not to be mediated by short-term scheduling of sensitive votes right after distracting events.
Keywords: D72; L82; L86; 330; Attention; campaign finance; interest groups; legislative voting; mass media; roll call voting; US House of Representatives